Ethics and Law : An Introduction - Wendel, W. Bradley (Cambridge : Cambridge University Press, 2014)
Can someone be a good person yet act in a professional role that may involve deception, procedural trickery, withholding information, and working on behalf of terrible people and institutions? This question is at the heart of legal ethics. Using cases from around the common-law world, W. Bradley Wendel looks at issues including confidentiality, the moral responsibility of lawyers, and truth and deception in advocacy. He then examines the classic questions of philosophy of law, including the nature of law, positivism, natural law, the relationship between law and morality, unjust legal systems, and the obligation to obey the law. Finally, he considers the ethical issues surrounding the role of lawyers, including criminal defense and prosecution, civil litigation, counseling clients on the law, and representing corporations. Combining the theoretical, philosophical, and practical, his book will be of vital interest to students of law, the philosophy of law, ethics, and political philosophy.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Keywords: Legal ethics